Draft Annual Plan 1989-90 Government of Meghalaya - Planning Commission (Planning Commission, 1989)
Meghalaya has an area of approximately 22, 500 sq. kms which accounts for 0.70 percent of the total landmass of India. The whole of the State is hilly with uneven topography. It comprises of 5 districts with 15 subdivisions. Meghalaya with a Population of 13.36 lakhs (0.19 per cent of India’s population) is one of the smallest in the country in terms of population as per 1981 Census.
Government of Meghalaya, Planning Department